2018
DOI: 10.1111/mve.12305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trapping method on species identification of phlebotomine sandflies by MALDI‐TOF MS protein profiling

Abstract: Sandflies (Diptera: Psychodidae) (Newstead, 1911) are blood-feeding insects that transmit human pathogens including Leishmania (Trypanosomatida: Trypanosomatidae) parasites, causative agents of the leishmaniases. To elucidate Leishmania transmission cycles, conclusive identification of vector species is essential. Molecular approaches including matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) protein profiling have recently emerged to complement morphological identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Additional trapping methods must also be considered, since light traps have sampling limitations [31] and multi-trapping approaches have been demonstrated to promote more representative sampling of the local species community [6]. Nevertheless, a previous study [16] showed that the sampling method must be taken into consideration because it can considerably impact the quality of proteic spectra, especially when using sticky traps. When compared with CDC light traps, the quality of the spectra obtained from sand fly specimens collected by sticky traps was always lower and did not allow correct identification.…”
Section: Discussionmentioning
confidence: 99%
“…Additional trapping methods must also be considered, since light traps have sampling limitations [31] and multi-trapping approaches have been demonstrated to promote more representative sampling of the local species community [6]. Nevertheless, a previous study [16] showed that the sampling method must be taken into consideration because it can considerably impact the quality of proteic spectra, especially when using sticky traps. When compared with CDC light traps, the quality of the spectra obtained from sand fly specimens collected by sticky traps was always lower and did not allow correct identification.…”
Section: Discussionmentioning
confidence: 99%
“…Although this technique is promising for mosquitoes’ identification, some parameters have to be considered prior to MALDI-TOF MS analysis. Indeed, previous studies on several arthropods have underlined the impact of trap type used for sampling, the preservation methods and the body part used for protein extraction on the spectra profile [ 23 26 ]. The impact of trapping duration on MALDI-TOF identification, however, has never been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…This probably means that a larger database may be needed to identify blood meals from several mosquito species. However, an increasing number of laboratories (Raharimalala et al, 2017;Halada et al, 2018;Mewara et al, 2018;Arfuso et al, 2019;Chavy et al, 2019;Rothen et al, 2016;Sambou et al, 2015;Yssouf et al, 2016) are applying MALDI-TOF to MS medical entomology and Raharimalala et al have also highlighted the need for sharing and have expressed interest in an international database (Raharimalala et al, 2017). Many reference spectra are also available on request or directly online (Lawrence et al, 2019), substantially facilitating database creation.…”
Section: Discussionmentioning
confidence: 99%
“…It has revolutionized clinical microbiology by making it possible to rapidly identify bacteria at a low cost (Seng et al ., 2009, 2013; Schubert and Kostrzewa, 2017). In recent years, the effectiveness of MALDI-TOF MS for identifying arthropods (Tandina et al , 2016, 2018a; Yssouf et al ., 2016; Diarra et al ., 2017; Laroche et al ., 2017 b ; Halada et al ., 2018; Mewara et al ., 2018) and mosquito blood meals identification (Niare et al 2016, 2017 b ; Tandina et al ., 2018 a , b ) has been reported. Indeed, in preliminary studies, MALDI-TOF MS was able to identify the host blood source from An.…”
Section: Introductionmentioning
confidence: 99%